Effect of Podcast towards Improvement of Students’ Listening Comprehension - Rahmi, Armita; Khulaifiyah, Khulaifiyah; Nawir, Erna; Ling, Zhang (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The integration of technology into educational practices has gained increasing attention, particularly in the realm of language learning. Podcasts, as a versatile and accessible digital tool, have emerged as a promising medium for enhancing various language skills. Employing experimental research, this investigation aims to determine whether the use of podcasts can significantly enhance students' listening abilities compared to traditional methods among eleventh-grade students at SMAN 3 Siak Hulu. Sample of 52 students was selected, divided into an experimental group (n=26) and a control group (n=26). The experimental group received treatment through audio podcasts, while the control group did not. Data were collected through pre-tests and post-tests, with essay-based assessments administered to evaluate listening comprehension. The experimental group's mean scores increased from 54.77 (pre-test) to 66.15 (post-test), while the control group's scores decreased from 64.12 (pre-test) to 53.85 (post-test). Statistical analysis using an independent sample t-test in SPSS 26 revealed a significant difference between the groups, with a t-test value of 2.741 (p = 0.008) surpassing the t-table value of 2.008. These results indicate a significant improvement in the listening comprehension of students exposed to podcasts, supporting the effectiveness of this technology in enhancing language learning outcomes. In brief, the study provides compelling evidence that incorporating podcasts into the educational curriculum significantly improves listening comprehension among students, thereby highlighting the potential of this technology to enhance language learning outcomes effectively.